LITERATUR REVIEW: PENGARUH ASI EKSLUSIF TERHADAP KEJADIAN STUNTING PADA BALITA - Awwalin, Jamilatul; Munir, Zainal (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
Stunting is one of the nutritional problems of toddlers with growth failure that has accumulated since before and after birth caused by inadequate intake of nutrients. Short toddlers (stunting) can be detected when a toddler has been measured for length or height, then compared with nutritional status based on length or height according to age when compared to the 2005 WHO-MGRS standard, the z-score value is less than -2SD and categorized as very short if the z-score is less than -3SD (Ministry of Health, 2016). Objective: To find out the effect of